Optical properties of CR-39 Detector Irradiated with Gamma-rays and (He-Ne) Laser - Tawfiq, Nada F; Neamah, Mohammed M; Rasheed, Essam M (Al-Nahrain Journal of Science, 2017)
The impacts of gamma-beams and He-Ne laser of optical properties for CR-39 track indicator were studied. Twenty locations separated into five gatherings. In the first-place aggregate, one finder un- irradiated (control). Second gathering, five indicators irradiated to 60Co gamma source with various dosages 300, 500, 800, 1200 and 1600 kGy (γ). Third gathering, 5 identifiers illuminated with gamma beam with various dosages 300, 500, 800, 1200 and 1600 kGy afterward presented to 15 min of He-Ne laser at 10 mW control (γ +laser). Fourth gathering, nine indicators were presented to various force 1, 5 and 10 mW of He-Ne laser at various circumstances 5, 10 and 15 min (laser). The optical properties were considered with bright unmistakable UV-visible and FTIR spectroscopic. In addition, the optical vitality band cavity and carbons number was computed at various gamma measurements and diverse time's introduction of He-Ne laser. The outcomes for second, third, fourth and fifth gatherings demonstrate expanding in the absorbance with expanding in the time presentation of He-Ne laser and gamma dose. The FTIR spectrum indicate moving in the groups of CR-39 track indicator presented to gamma beam, laser and (γ +laser), for gamma beam demonstrate expanding in the absorbance at 300 kGy and unsymmetrical diminishing of absorbance at 500-1600 kGy, and for CR-39 identifier presented to (γ +laser), the impacts demonstrate unsymmetrical diminishing in the force absorbance with increment in the gamma measurements, at laser impacts indicate expanding in the absorbance A, with expanding in the time introduction of He-Ne laser at various forces